CLINICAL CASE OF PERFORMING A TWO-ST AGE LOVER RESECTION BY TYPE ALPPS IN PATIENT WHO PREVIOUSLY UNDERWENT ANATOMIC RESECTION OF THE RIGHT LOBE OF THE LIVER - D. V. Sidorov; M. V. Lozhkin; L. O. Petrov; N. A. Grishin; A. A. Troitskiy; L. I. Moskvicheva (Исследования и практика в медицине, 2015)
Abstract:One of the variants for the surgical treatment of patients with bilobal liver metastases is to perform two-stage anatomic resections. Thus, at least in a quarter of the patients it is impossible to perform the second stage of intervention because of absence of hypertrophy of the remaining liver parenchyma or progression of disease during standby. The most modern and promising way of overcoming this obstacle is to perform the so-called ALPPS (Associating Liver Partition and Portal vein Ligation for Staged hepatectomy) or «in situ slit» liver resections. In this article we present a clinical case of performing a two-stage hepatectomy by type ALPPS in patients with metastatic colorectal cancer liver, who previously undergone the anatomic bisegmentectomy SVI-SVII. The present observation is the first in the available literature, evidence of justification perform repeated liver resections in patients with metastatic colorectal cancer and demonstrates the possibility of ALPPS techniques when performing extensive anatomical liver resections in patients who have undergone previous removal of the parenchyma of the right lobe.